RANCANG BANGUN ALGORITMA OBSTACLE AVOIDANCE ROBOT INSPEKSI MENGGUNAKAN SENSOR ULTRASONIK DAN LOGIKA FUZZY - Mohammad Rizanto Juliarsyah; Faradilla Fauziyah Risnawati (MULTITEK INDONESIA, 2025)
Underground channels are subject to limited manual inspection owing to the fact that it is inefficient, high risk, and labor-intensive. These make obstacle-avoiding robots crucial in inspecting channels. This paper aims at designing an obstacle avoidance algorithm with ultrasonic sensors and fuzzy logic for enabling the free movement of inspection robots. The research approach includes the establishment of a fuzzy control system that accepts ultrasonic sensor distance input and provides decisions on robot movement direction. The two defuzzification strategies utilized in assessing the performance of the algorithms include Center of Maximum (COM) and Mean of Maximum (MOM). Testing included the presentation of various obstacle situations in front and along the robot. The result was that the Center of Maximum (COM) method created more precise straight and turn movements, yet at times the direction of motion was less consistent. In contrast, the Mean of Maximum (MOM) method could create a faster and more stable reaction to position change even when creating tighter turns. Overall, the system designed was successful in improving navigation capability of the inspection robots in confined spaces and could potentially serve as a base to develop more from for real-world applications in the field.